REFORM OF HOUSING COMMUNAL SERVICES IN UZBEKISTAN - Primova Shahnoza Komiljonovna; Mamatkulov Murodjon Shukurovich (American Journals Publishing, 2023)
The article talks about the radical change in the methods and approaches of financing and management of the housing reform and the related scientific proposals and practical recommendations.
Keywords: housing and communal services, housing owners' service, housing code, multi-story buildings, multi-apartment buildings.